Nexus between Human Resource Development. Poverty and Self-employment: A Sustainable Business for Rural Poor - Bashyal, Rama (Economic Journal of Nepal, 2011)
Human resource development can be viewed broadly by underdeveloped economies as their strategy for poverty alleviation. The large numbers of unemployed and underemployed rural people are the hidden resources of these countries. If thq are accessed to micro financial services, it will be a support for getting them out of both economic and Mown poverty through increasing their incomes, food sufficiency level and investment in children’s education. Microfinance has also been proved to be a stable business for millions of micro clients than for the clients of traditional .finance even at the time of financial crisis (Indonesia’s case 1997). Even at the time of current global financial crisis, the process of poverty reduction depends upon the enhancement of opportunity for poor people through increasing sellemployment, increasing productivity from self-employment, and increasing income from self-employment businesses and thereby reducing the poverty. Key words: Human resources; Poverty; Sustainable business; Rural poor Economic Journal of Nepal A Quarterly Publication of the Central Department of Economics T.U., Kirtipur Vol. 32, No. 1 January-March 2009, Issue No. 125 Page: 14-23 Uploaded date: 5 July 2011